DESCRIPTION OF TOTAL PLATE COUNT OF BINGKA CAKE SOLD IN SAMARINDA CITY - Andira, Ayu; Harlita, Tiara Dini; Anggrieni, Nurul (Journal of Medical Laboratory and Science, 2023)
Background: Bingka cake is a type of wet cake made from a mixture of flour, eggs, brown sugar and coconut milk. Wet cakes are generally prone to health risks because sometimes the handling is not hygienic and can cause the possibility of this cake being contaminated with bacteria. Bacterial contamination in food can be a medium for a disease, this disease is commonly called foodborne disease. The purpose of this study was to determine the Total Plate Number (ALT) of Bingka cakes sold in Samarinda City. Methods: The type of research used in this research is descriptive. The examination carried out was the total plate number using the pour plate method on 15 samples of brown sugar cakes sold in Samarinda City. 10 grams of brown sugar cake sample was taken, then dilution was carried out with 3 levels and a total of 45 treatments. Then the sample that has been diluted is poured into a petri dish as much as 1 ml. After that, pour 15-20 ml of PCA media into the petri dish containing the diluted sample. Then incubated in the incubator for 48 hours and then counted the colonies using a colony counter. After the calculations were carried out, it was continued with univariate data analysis. Results: The results showed that of the 15 samples examined, the results met the quality standard requirements of SNI 01-4309-1996, namely (1 × 106) CFU/g with a percentage of 100% Fulfillment. The highest germ count was found in samples with code N, namely (5.3×104 CFU/g) and the lowest germ numbers in samples with codes F and L, namely (8×101 CFU/g). Conclusion: In this study it can be concluded that Bingka cake sellers use good quality raw materials. The presence of bacterial colony growth that occurs in these samples can be contaminated during post-processing. In addition, the environment around when selling is too close to exposure to dust, roads where vehicles pass and trash cans.